MPLS advantages for traffic engineering. - Swallow, G. (IEEE Communications magazine)
This article discusses the architectural aspects of MPLS which enable it to address IP traffic management. Specific MPLS architectural features discussed are separation of control and forwarding, the label stack, multiple control planes, and integrated IP and constraint-based routing. The article then discusses how these features address network scalability, simplify network service integration, offer integrated recovery, and simplify network management. Scalability is addressed through integrated routing enabling a natural assignment of traffic to the appropriate traffic engineering tunnels without requiring special mechanisms for loop prevention. Change is greatly reduced. The label stack enables an effective means for local tunnel repair providing fast restoration. Feedback through the routing system permits fast and intelligent reaction to topology changes. Service integration is simplified through a unified QoS paradigm which makes it simple for services to request QoS and have it mapped through to traffic engineering